2022
DOI: 10.2147/jir.s351913
|View full text |Cite|
|
Sign up to set email alerts
|

Benzimidazole Derivatives as New Potential NLRP3 Inflammasome Inhibitors That Provide Neuroprotection in a Rodent Model of Neurodegeneration and Memory Impairment

Abstract: The study investigated the effect of newly synthesized benzimidazole derivatives against ethanol-induced neurodegeneration. According to evidence, ethanol consumption may cause a severe insult to the central nervous system (CNS), resulting in mental retardation, neuronal degeneration, and oxidative stress. Targeting neuroinflammation and oxidative stress may be a useful strategy for preventing ethanol-induced neurodegeneration. Methodology: Firstly, the newly synthesized compounds were subjected to molecular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The level of NLRP3 in the intestinal tissue of infected mice that were given either ABZ or KPF decreased. The inhibitory effect of ABZ on NLRP3 was documented previously, and the suggested mechanism is via nuclear factor kappa B inhibition, which regulates the expression of NLRP3, caspase 1 and pro-interleukin-1β (pro-IL-1β) (Ullah et al , 2022). For KPF, the inhibitory effect on NLRP3 is through inhibition of IL-1β production and apoptosis-associated speck-like protein containing caspase recruitment domain oligomerization (Lim et al , 2018).…”
Section: Discussionmentioning
confidence: 91%
“…The level of NLRP3 in the intestinal tissue of infected mice that were given either ABZ or KPF decreased. The inhibitory effect of ABZ on NLRP3 was documented previously, and the suggested mechanism is via nuclear factor kappa B inhibition, which regulates the expression of NLRP3, caspase 1 and pro-interleukin-1β (pro-IL-1β) (Ullah et al , 2022). For KPF, the inhibitory effect on NLRP3 is through inhibition of IL-1β production and apoptosis-associated speck-like protein containing caspase recruitment domain oligomerization (Lim et al , 2018).…”
Section: Discussionmentioning
confidence: 91%
“…The scaffold of 1 and 2 consists of a disubstituted benzimidazole. Throughout the years, the benzimidazole moiety has been used as a scaffold to synthesize a wide variety of compounds involved in biological processes; in the literature, many examples support the antioxidant properties and neuroprotective role of derivatives from this class [21,22]. Notably, 3 and 4 have similar motifs formed by two condensed rings bearing nitrogen atoms.…”
Section: Resultsmentioning
confidence: 99%
“…The Morris water maze test can be used to study dysfunction of learning and memory ability ( 35-40 ). Increased expression levels of pro-inflammatory factors contribute to dysfunction of learning and memory ability ( 26 , 27 ). In the present study, the night-time Morris water maze training and test experiment indicated that the memory dysfunction in the model rats was accompanied by a longer escape latency and reduced number of times crossing the target regions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the levels of inflammatory cytokines, namely IL-1, IL-6, TNF-α and IL-10, are affected by insomnia (25). The abnormal levels of these cytokines further affect brain function, such as learning and memory (26,27). Furthermore, orexin A and its receptors play important roles in the regulation of food intake, circadian rhythms, arousal and sleep (28)(29)(30)(31)(32).…”
Section: Establishment Of a Chronic Insomnia Rat Model Of Sleep Fragm...mentioning
confidence: 99%